Associations between blood heavy metal(loid)s and serum heme oxygenase-1 in pregnant women: Do their distribution patterns matter?. (1st October 2021) - Li, Kexin; Wang, Bin; Yan, Lailai; Jin, Yu; Li, Zhiyi; An, Hang; Ren, Mengyuan; Pang, Yiming; Lan, Changxin; Chen, Junxi; Zhang, Yali; Zhang, Le; et al.
Abstract: The relationship between heavy metal(loid)s exposure and oxidative stress damage is a matter of research interest. Our study aimed to investigate the distribution patterns of the nine heavy metal(loid)s in blood of pregnant women, including four toxic heavy metal(loid)s [arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg)] and five typical heavy metal(loid)s [manganese (Mn), cobalt (Co), copper (Cu), zinc (Zn), and selenium (Se)] in blood. Blood samples of 348 women were collected and their concentrations in the serum (sr) and blood cells (bc) were measured, as well as serum heme oxygenase-1 (HO-1) (an oxidative stress marker). Total blood (tb) concentrations of these metal(loid)s and serum-to-blood cell concentration ratios (sr/bc) were further calculated. We found Cu mainly accumulated in the serum compared to the blood cells with Cu sr/bc  = 2.30, whereas Co, Se, and As evenly distributed between these two fractions. Other metal(loid)s mainly concentrated in the blood cells. Co sr, Cu sr, Cu bc, Mn bc, Zn bc, Cd bc, Co tb, Cu tb, Mn tb, Zn tb, Cd tb, and Cu sr/bc were negatively associated with serum HO-1, whereas As sr, As bc, As tb, Zn sr/bc, Cd sr/bc, and Hg sr/bc were positively, indicating of their potential toxicity. We concluded that the distribution patterns of blood heavy metal(loid)s, in particular for Cd, Hg and Zn, which either increased in serum or decreased in blood cells, might be associated with elevated serum oxidative stress, should be considered in environmental health assessments. Graphical abstract: Image 1 Highlights: We measured maternal concentration ratios of metals in serum-to-blood cell (sr/bc). Associations of blood metals' distribution patterns with serum HO-1 were examined. Relations between blood metals and serum HO-1 varied with their distributions. Cd sr/bc, Hg sr/bc, and Zn sr/bc were positively associated with serum HO-1 level. Blood metal distribution pattern should be considered for their health assessment. Abstract : Blood heavy metal(loid)s distribution patterns may affect their relationships with oxidative stress and should be considered in environmental health assessments.